2012
DOI: 10.1177/1476718x11430071
|View full text |Cite
|
Sign up to set email alerts
|

Translation and use of parent-completed developmental screening test in Shanghai

Abstract: As part of efforts throughout China to improve the outcomes of individuals with disabilities, the Shanghai government has launched a campaign to screen at least 95 percent of newborns. To assist in meeting this goal, the Ages & Stages Questionnaires (ASQ), Third Edition, was translated into Chinese and the feasibility of a screening system using the ASQ-Chinese translation (ASQ-C) was investigated in Shanghai. Twenty-nine primary children’s healthcare clinics and several district-wide children’s healthcare ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 20 publications
(30 reference statements)
1
33
0
Order By: Relevance
“…Total sample sizes varied extensively, from 60 (Saihong ) to 45 640 (Filgueiras ), but most (72%, n = 13) ranged between approximately 100 and 3000 participants. Studies comprised convenience samples (Pomes ; Filgueiras ; Saihong ; Veldhuizen et al ), at‐risk groups (San Antonio et al ), non‐representative samples (Ivey‐Soto ; Kucuker et al ), stratified random samples (Heo ; Squires et al ; Squires et al ; Bian et al ; Heo & Squires ; Filgueiras ) and representative samples (de Wolff et al ; Filgueiras et al ; Kvestad et al ; Schonhaut et al ; Lopes et al ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total sample sizes varied extensively, from 60 (Saihong ) to 45 640 (Filgueiras ), but most (72%, n = 13) ranged between approximately 100 and 3000 participants. Studies comprised convenience samples (Pomes ; Filgueiras ; Saihong ; Veldhuizen et al ), at‐risk groups (San Antonio et al ), non‐representative samples (Ivey‐Soto ; Kucuker et al ), stratified random samples (Heo ; Squires et al ; Squires et al ; Bian et al ; Heo & Squires ; Filgueiras ) and representative samples (de Wolff et al ; Filgueiras et al ; Kvestad et al ; Schonhaut et al ; Lopes et al ).…”
Section: Resultsmentioning
confidence: 99%
“…As well as its use in North America, it has been translated and used around the world; e.g. Europe (Kerstjens et al ; Sarmiento Campos et al ; Troude et al ; Østergaard et al ; Sidor et al ; Lopes et al ), Asia (Bian et al ; Saihong ; Bian et al ; Heo & Squires ; Juneja et al ), South America (Filgueiras et al ; Schonhaut et al ) and Australia (D'Aprano et al ).…”
Section: Introductionmentioning
confidence: 99%
“…factor analysis, item analysis, etc.) . Two studies reported on the ASQ's relation to other measures via correlations with a criterion measure .…”
Section: Resultsmentioning
confidence: 99%
“…factor analysis, item analysis, etc.). 33,[46][47][48][49][50][51][52][53][54][55][56][57][58] Two studies reported on the ASQ's relation to other measures via correlations with a criterion measure. 49,50 Finally, six studies reported on the consequences of ASQ use.…”
Section: Psychometric Studiesmentioning
confidence: 99%
See 1 more Smart Citation